Characteristics of postoperative management of patients after microendolaryngeal laser resection of malignant tumor of the voice box - N. A. Daikhes; V. V. Vinogradov; S. S. Reshulskii; R. R. Khabiev; E. B. Fedorova; M. L. Isaeva; S. M. Kochieva; K. V. Mishchenko (Опухоли головы и шеи)
Introduction. Internation and Russian experience of surgical treatment of stage T1–2N0m0 laryngeal cancer in the form of endolaryngeal laser resection demonstrates good oncological and functional results. The problem of patient management in the postoperative period after these surgical interventions remains unsolved.Aim. To determine rational tactics of postoperative management of patients with cancer of the voice box after microendolaryngeal laser resection.Materials and methods. The study included 50 patients with squamous cell carcinoma of the voice box aged between 31 and 84 years who received treatment at the Head and Neck Oncology Division of the National medical Research Center for Otorhinolaryngology between 2022 and 2025. All patients underwent surgical treatment – endolaryngeal laser resection. Depending on the resection volume, the patients were divided into 2 groups. group 1 included 30 (60 %) patients with stage Tis–1aN0m0 laryngeal cancer who underwent type II–III cordectomy; group 2 included 20 (40 %) patients with stage T1b–3N0m0 laryngeal cancer who underwent type IV–VI cordectomy. Cordectomy volume was evaluated in accordance with the classification of the European Laryngological Society (ELS). At day 21–23, the patients were hospitalized again. Endoscopic evaluation of the postoperative wound, microdebrider procedure, histological examination of granulation tissue and bacteriologic examination of the material near the surgical area were performed.Results. In group 2, increased production of dirty yellow exudate, thick fibrin layer on the wound surface, marked hyperemia and edema of the laryngeal mucosa, contamination of the surgical area (more frequent than in group 1) by highly pathogenic microorganisms with high titers were observed. Histological differences in granulation tissue between groups 1 and 2 show marked inflammation and tendency towards prolonged healing.Conclusion. Taking into account the obtained data, an algorithm of postoperative management of patients was developed to decrease complication rate, the number of unsatisfactory functional results, and therefore decrease patient rehabilitation time.